Effect of Various Sodium Chloride Mass Fractions on Wheat and Rye Bread Using Different Dough Preparation Techniques - Marta Ambrosewicz-Walacik; Małgorzata Tańska; Daniela Rotkiewicz; Andrzej Piętak (Food Technology and Biotechnology, 2016)
This study assessed the selected properties of bread with reduced amount of sodium chloride. The bread was made from white and wholemeal wheat flour and rye flour. The dough was prepared using three techniques: with yeast, natural sourdough or starter sourdough. Sodium chloride was added to the dough at 0, 0.5, 1.0 and 1.5 % of the flour mass. The following bread properties were examined in the study: yield and volume of the loaf, moisture content, crumb firmness and porosity, and organoleptic properties. Reducing the mass fraction of added sodium chloride was not found to have considerable effect on bread yield, whereas it had a significant and variable effect on the loaf volume, and crumb firmness and porosity. Organoleptic assessment showed diverse effects of sodium chloride addition on sensory properties of bread, depending on the type of bread and the dough preparation method. Reduced mass fractions of sodium chloride changed the organoleptic properties of bread made with yeast and with starter sourdough to a greater extent than of bread prepared with natural sourdough.